Spontaneous Intermolecular Amide Bond Formation between Side Chains for Irreversible Peptide Targeting - Zakeri, Bijan; Howarth, Mark (Journal of the American Chemical Society, 2010)
Peptides and synthetic peptide-like molecules are powerful tools for analysis and control of biological function. One major limitation of peptides is the instability of their interactions with biomolecules, because of the limited accessible surface area for noncovalent interactions and the intrinsic flexibility of peptides. Peptide tags are nonetheless fundamental for protein detection and purification, because their small size minimizes the perturbation to protein function. Here we have designed a 16 amino acid peptide that spontaneously forms an amide bond to a protein partner, via reaction between lysine and asparagine side chains. This depended upon splitting a pilin subunit from a human pathogen, Streptococcus pyogenes, which usually undergoes intramolecular amide bond formation to impart mechanical and proteolytic stability to pili. Reaction of the protein partner was able to proceed to 98% conversion. The amide bond formation was independent of redox state and occurred at pH 5−8. The reaction was efficient in phosphate buffered saline and a wide range of biological buffers. Surprisingly, amide bond formation occurred at a similar rate at 4 and 37 °C. Both peptide and protein partners are composed of the regular 20 amino acids and reconstituted efficiently inside living E. coli. Labeling also showed high specificity on the surface of mammalian cells. Irreversible targeting of a peptide tag may have application in bioassembly, in cellular imaging, and to lock together proteins subject to high biological forces.